(untitled) (United Journal of Interdisciplinary Studies, 2024)
This study aims to investigate the determinants of e-banking adoption in Nepal using the Technology Acceptance Model (TAM) as a theoretical framework. In recent years, e-banking has gained traction as a convenient and efficient way to conduct financial transactions, but its adoption in Nepal remains relatively low. The purpose of this study was to identify the factors determining individuals’ decisions to adopt e-banking services in Nepal, with a focus on convenience, time savings, security, and communication. A quantitative research approach was employed, utilizing a descriptive research design. Data was collected through a structured questionnaire distributed to e-banking users at various banks in the Kathmandu district. The study found that convenience and time savings were significant determinants of e-banking adoption, supported by statistically significant one-sample t-test results. However, security shown a non-significant impact, while communication demonstrated a significant but slightly lower effect. Therefore, it is recommended that financial institutions in Nepal prioritize enhancing convenience and time-saving features in their e-banking platforms to encourage greater adoption among customers. Additionally, efforts should be made to improve communication strategies to effectively convey the benefits and security measures of e-banking, thereby addressing concerns and building trust among potential users.